Interest In Buying Millennial Generation Electric Motorcycles with Theory of Planned Behaviour and Environmental Concern as Determining Factors - I Made Gde Pasek Bagiartana; I Nyoman Rasmen Adi (PT Mattawang Mediatama Solution, 2023)
The solution of environmental problems is to use environmentally friendly products. This research uses the theory of planned behaviour, norm activation model, and moral norm as mediating variables to test consumers' interest in purchasing electric motorcycle. Data collected from 157 respondents who are the millennial generation and analyse with SmartPLS 3.0. Based on research findings, environmental concern has a significant effect on perceived behavioural control, green purchase attitude, and green purchase intention. Perceived behavioural control has a significant effect on green purchase attitude. Moral norms and green purchase attitude do not have a significant effect on green purchase intention. Then moral norms cannot mediate between subjective norms and green purchase intention. Research findings explain that environmental factors are the determining factor for someone to adopt an electric motorcycle.